The Determinant Factors of Behavior Intention and Trust in Digital-Only Bank: Gen-Z Perspective - Cindy Alfirdausi; Cut Aprilia (Yayasan Sagita Akademia Maju, 2025)
This study aims to examine the driving factor of trust and behavior intention toward digital-only banks from a Gen-Z perspective. It investigates the effect of perceived security, awareness, and trust on the intention to adopt the digital-only bank. It also investigates the influence of perceived security and awareness on trust in digital-only banks. The sample used was 170 respondents of Management Department students at the University of Syiah Kuala. The data was collected using an online questionnaire. PLS-SEM was used for data analysis. The result showed that perceived security and trust influence users’ intention to adopt digital-only banking. This study also found that trust is influenced by perceived security. Although awareness does not influence users’ intentions, it contributes to creating users' trust in digital-only bank leading them to adopt the service. Therefore, it is suggested that the bank educate the targetted users about the benefits and security system of digital-only banks